HUBUNGAN KECEPATAN DAN KEKUATAN OTOT TUNGKAI TERHADAP KEMAMPUAN SHOOTING SSB TARUNA MANDIRI U-17 PEKANBARU - ', Taufik; ', Saripin; Juita, Ardiah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: Based on the observations of the authors in the field since the founding of SSB Youth Self U-17 Pekanbaru from 2010 until the present has not received the maximum results it can be seen from the results of the game that is often followed by SSB Youth Self U-17 Pekanbaru, one of which is on Shooting moment. The objective in this study was to examine the relationship of speed and leg muscle strength with the ability of the player shooting pigeons SSB Youth U-17 Pekanbaru. The population in this study are all registered athletes in SSB Independent Youth U-17 That amounts to 24 people. The sampling technique in this research is to use the total sampling technique. The sample was 24 people. Data collection techniques required in this study is the measurement of the two variables do is measure the speed with a run of 40 yards, with leg leg muscle strength dynamometer and shooting using kegawang shooting. Data collected in the analysis using simple and multiple produt moment. Based on the research that the results obtained are related to the accuracy of speed shooting in a football game SSB Independent Youth U-17 Pekanbaru is the acquisition rhitung (-0.672)> of acquisition rtabel (-0.482) at α = 0.05. then the results obtained have a leg muscle strength in relation to the accuracy shooting football game SSB Independent Youth U-17 Pekanbaru is the acquisition rhitung (0.632)> from the acquisition rtabel (0.482) at α = 0.05. An association was jointly between leg muscle strength and speed of the accuracy of shooting in the game of football SSB Independent Youth U-17 Pekanbaru is the acquisition rhitung (0.769)> from the acquisition rtabel (0.482) at α = 0.05.Keywords: Speed, Strength Muscle Limbs and Shooting